Xanthomatous Hypophysitis: A Case Report and Comprehensive Literature Review - Zhu, Jianyu; Wang, Zhicheng; Wang, Wenze; Fan, Jinghua; Zhang, Yi; Li, Xiaoxu; Liu, Jie; Jiang, Shenzhong; Deng, Kan; Duan, Lian; Yao, Yong; Zhu, Huijuan (Frontiers in Endocrinology, 2021)
Purpose: Xanthomatous hypophysitis (XHP) is an extremely rare form of primary hypophysitis for which there is a lack of clinical experience. A comprehensive understanding of its clinical characteristics, diagnosis and treatment is needed. Methods: Here, we report a case study and conduct a systematic review of XHP. Thirty-six cases were included, and their clinical manifestations, endocrine assessment, imaging features, treatment and follow-up data were collected and analyzed. Results: The mean age at diagnosis was 39.1 years, and females were predominant (75.0%). The most common symptom was headache (68.6%), and 66.7% of female patients presented menstrual disorders. The most common pituitary dysfunction was growth hormone (GH) deficiency. More than half of patients exhibited central diabetes insipidus (CDI). The majority of patients had an imaging presentation of a cystic lesion with peripheral enhancement. Pituitary stalk thickening was observed in half of the patients. Total lesion resection was achieved in 57.1% of cases. The recurrence rate after partial resection and biopsy was significantly higher than that after total lesion resection (57.1% vs. 0.0%, P = 0.0147). The most common pituitary hormone abnormalities to resolve after surgery were hyperprolactinemia (100.0%) and GH deficiency (91.7%). The typical pathological feature was inflammatory infiltration of foamy histiocytes, which showed positivity for CD68. Conclusion: Diagnosis of XHP is difficult when relying on clinical symptoms and imaging features. Therefore, surgical histopathology is necessary. Based on the available evidence, total lesion resection is recommended for treatment. However, the long-term prognosis for this rare disease remains unclear.